Analisis Faktor dan Solusi Kasus Kekerasan terhadap Guru: Perspektif Al-Qur'an - Lukman Nol Hakim (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The phenomenon of violence against teachers in schools has become a serious issue in contemporary education, as it affects teachers’ psychological well-being, the quality of educational relationships, and the effectiveness of learning processes. Although studies on school violence have developed extensively, limited attention has been given to teachers as victims and to the integration of Islamic educational perspectives based on the Qur’an. This study aims to: (1) identify internal and external factors that trigger violence against teachers, (2) examine Qur’anic verses and Islamic educational principles related to teacher–student ethical relations, and (3) formulate an integrated solution framework for institutional policies and school practices. This research employs a qualitative approach using library research, applying a thematic (maudhu’i) interpretation method and utilizing content analysis and thematic analysis of primary sources (the Qur’an and tafsir) and secondary scholarly literature.The findings indicate that violence against teachers is influenced by three main factors: individual factors (low emotional regulation and self-control), structural-institutional factors (weak governance and inadequate teacher protection), and socio-cultural factors (value shifts and weakened ethical internalization). The Qur’anic perspective emphasizes the principles of ta‘zhim (respect for people of knowledge), ihsan in communication, and ‘adl (justice) as the foundation of teacher–student relations. The integration of Qur’anic values into character education, teacher protection policies, and a school culture grounded in rahmah (compassion) provides a transformative framework to systematically and sustainably reduce violence against teachers.